Optimizing Physical Performance and Nutritional Strategies for Young Basketball Players: Training Load Distribution and Recovery Approaches - Mara, Ferdinand; Plasa, Migena (International Journal of Child Health and Nutrition, 2025)
Background: This study examines the optimization of physical load distribution in young basketball players while integrating nutritional strategies to enhance performance, recovery, and overall health. Proper nutrition supports endurance, muscle function, injury prevention, and physiological development in young athletes, making it essential in conjunction with structured training. Method: This study employs a scoping review methodology to analyze recent literature on the physical performance and nutrition of young basketball players. It synthesizes findings from studies published between 2014 and 2024, focusing on training strategies, nutritional practices, and their impact on the physical development of athletes. The review examines factors such as exercise routines, hydration, macronutrient and micronutrient intake, and post-exercise recovery strategies to optimize performance and ensure long-term health for youth athletes. Results: The review identifies key factors that influence youth basketball performance, including structured training, proper nutrition, and hydration. It emphasizes the importance of balanced macronutrient intake and targeted interventions to enhance strength, endurance, and recovery, thereby optimizing physical development. Conclusions: A holistic approach that combines structured training with tailored nutrition plans is essential for enhancing youth basketball performance and promoting long-term health.